Perubahan Bentuk P Oleh Mikroba Pelarut Fosfat dan Bahan Organik Terhadap P-tersedia dan Produksi Kentang (Solanum tuberosum L.) pada Tanah Andisol Terdampak Erupsi Gunung Sinabung - Marta Ritonga; Bintang Sitorus; Mariani Sembiring (Jurnal Agroekoteknologi, 2016)
Andisol was soil with high phosphate retension (>85 %) so that Phosphate not available to plants. Phosphate (P) was important nutrient that used in photosynthesis process, roots growth, flower, fruit and seed forming. The object of this research is to know the effect of phosphate solubilizing microbe (MPF) application, some organic matter sources and both of interaction to changes of phosphate form to phosphate availability and potatos (Solanum tuberosum L.) production at Andisol soil impacted Sinabung Mountain eruption. This research was conducted in Kuta Rakyat Village, Naman Teran Subdistrict, Karo Regency on February until July 2015. The research used factorial Random Device Group Methode (RDG) consists of two treatments and two replications. The first factor is phosphate solubilizing microbe with four treatments: control, phosphate solubilizing bacterial (30 ml), phosphate solubilizing fungi (30 ml), phosphate solubilizing bacterial and fungi (15 ml + 15 ml). The second factor is organic matter with five treatments: control, cow manure (100 g/plant), chicken manure (100 g/ plant), straw (100 g/ plant), Tithonia diversifolia (100 g/ plant). The result showed that phosphate solubilizing fungi and chicken manure application, increased P availability and productions of potato (Solanum tuberosum L.) plants.Key Words : Andisol, Phosphate solubilizing microbe, organic matter, availability phosphate,production of potatos (Solanum tuberosum L.)Andisol was soil with high phosphate retension (>85 %) so that Phosphate not available to plants. Phosphate (P) was important nutrient that used in photosynthesis process, roots growth, flower, fruit and seed forming. The object of this research is to know the effect of phosphate solubilizing microbe (MPF) application, some organic matter sources and both of interaction to changes of phosphate form to phosphate availability and potatos (Solanum tuberosum L.) production at Andisol soil impacted Sinabung Mountain eruption. This research was conducted in Kuta Rakyat Village, Naman Teran Subdistrict, Karo Regency on February until July 2015. The research used factorial Random Device Group Methode (RDG) consists of two treatments and two replications. The first factor is phosphate solubilizing microbe with four treatments: control, phosphate solubilizing bacterial (30 ml), phosphate solubilizing fungi (30 ml), phosphate solubilizing bacterial and fungi (15 ml + 15 ml). The second factor is organic matter with five treatments: control, cow manure (100 g/plant), chicken manure (100 g/ plant), straw (100 g/ plant), Tithonia diversifolia (100 g/ plant). The result showed that phosphate solubilizing fungi and chicken manure application, increased P availability and productions of potato (Solanum tuberosum L.) plants.Key Words : Andisol, Phosphate solubilizing microbe, organic matter, availability phosphate,production of potatos (Solanum tuberosum L.)